2018
DOI: 10.1136/bmj.k3649
|View full text |Cite
|
Sign up to set email alerts
|

Stop smoking services: BMJ analysis shows how councils are stubbing them out

Abstract: Cash strapped councils have slashed smoking cessation budgets in England again this year, The BMJ has found. As some areas dispense with them entirely, Gareth Iacobucci examines whether these services are withering on the vine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…Last August a BMJ investigation found that half of local authorities in England had cut their stop smoking budgets in 2018-19,2 a continuing trend driven by government reductions to public health budgets.…”
mentioning
confidence: 99%
“…Last August a BMJ investigation found that half of local authorities in England had cut their stop smoking budgets in 2018-19,2 a continuing trend driven by government reductions to public health budgets.…”
mentioning
confidence: 99%
“…We are surprised that unproven and potentially dangerous e-cigarettes are being promoted at a time when there have been substantial cuts to successful public health services, including smoking cessation services 89…”
mentioning
confidence: 99%
“…This comes as shrinking local authority budgets mean smoking cessation services downsize or disappear,3 showing the limitations of organisational approaches. One step forward, two steps back.…”
mentioning
confidence: 99%